Growth variation, heritability and genetic gain in the firstgeneration of shorea leprosula progeny test at Kemasul Forest Reserve, Pahang, Malaysia - Abdullah, Mohd-Zaki; Wook, Nor-Fadilah; Rajoo, Keeren Sundara; Lias, Muhammad-Asri (2021)
Shorea leprosula is a tree species endemic to Southeast Asian rainforest that is highly valued for its timber and resin. Therefore, it has potential to be grown in forest plantations. To achieve this, a tree improvement program was conducted via a progeny trial, consisting of 40 half-sib families planted at Kemasul Forest Reserve (FR), Pahang, Malaysia. The main objectives were to evaluate the growth performances of S. leprosula progeny test based on selected growth traits and to estimate the values of heritability and genetic gain. The progeny trial plot was established with 40 half-sib families that originated from 5 populations. The trial plot was laid out in a randomized complete block design (RCBD) with 8 blocks and 4 trees planted per block making the total planted trees amounting to 1280 with a total area of 2.05 hectare. This paper will discuss the variations in the growth performances, heritability (h2) and genetic gain (∆G) estimated from the following growth traits; diameter at breast height (DBH), total height (HT), clear bole height (CBH), mean crown radius (MCR), crown class, stem form, branch angle, branch size and forking characteristics. Findings showed that the survival rate (47.1%) of S. leprosula progeny test in Kemasul FR was relatively low due to an inevitable factor such as disturbance from wild elephant. In addition, the growth variations observed were significantly high (p < 0.05) among the important economic traits such as DBH, HT and CBH. Besides, there were high variations observed within the progenies and among the 40 half-sib families. There were five families (F5, F4, F18, F1 and F28) that performed well based on the ordinal ranking. These five families originated from Menyala River FR and Gombak FR. On the other hand, based on the estimation of heritability (h2) and genetic gain (∆G), the HT trait showed the highest value indicating that this trait could be considered as an important trait in family selection. Furthermore, findings in this study have managed to provide important fundamental knowledge in establishing a seedling seed orchard for S. leprosula.